Efficient Two-Stage Meso- and Thermophilic Anaerobic Digestion of Food Waste from a Microbial Perspective - Katsuaki Ohdoi; Yoshihiro Okamoto; Tomonori Koga; Haruka Takahashi; Mugihito Oshiro; Toshihito Morimitsu; Hideki Muraoka; Yukihiro Tashiro; Kenji Sakai (Fermentation)
Two-stage meso- and thermophilic anaerobic digestion (TSMTAD) of food waste was examined and its microbiological structure was investigated. The first stage was designed for the primary storage of perishable food waste and the second stage for central biogas production. Mesophilic storage with initial neutralization and inoculation of lactic acid bacteria (LAB) resulted in an accumulation of lactic acid (21–23 g/L) with a decreased pH, in which bacterial members in facultative hetero-fermentation-type LAB dominated. Repeated fed-batch storage showed stable accumulation of lactic acid, retaining 89.3% (av.) carbon and preventing the growth of exogenous food pathogens. When the second stage of TSMTAD was compared with direct single-stage anaerobic digestion (SSAD) at 55 °C, the amount of methane accumulated was 1.48-fold higher (896 NmL/g-vs.). The methane yield of the original food refuse was 6.9% higher in the case of TSMTAD. The microbial community structures of both cases were similar, consisting of a sole thermophilic hydrogen-assimilating methanogen, Methanothermobacter thermautotrophicus. However, the abundance of bacteria belonging to two functional groups, H2 CO2 and acetic acid producer, and syntrophic acetate-oxidizing bacteria increased in TSMTAD. This may change the metabolic pathway, contributing to the stimulation of methane productivity.